Uji Aktivitas Antioksidan dari Ekstrak Buah Sentul (Sandoricum koetjape Merr.) - Faizul Bayani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2016)
Sentul fruit (Sandoricum koetjape Merr.) is representing one kind of fruit that is amount enough abundance at West Nusa Tenggara, but it hasn’t been exploited in an optimal fashion and more castaway useless. Parts of Sentul plant have been applied as traditional medicine. Sentul fruit can be oxidated by the browning reaction when it is pared or sliced, these symptoms showed the existences of phenolic compounds so that very potential as an antioxidant. To analyze the total phenolic and antioxidant activity of methanol extract of Sentul fruit, the Folin-Ciocalteu and DPPH methods have been used. Results of analysis for three treatment types of samples ( A, B, and C) shown their total phenolic: 6,9 %, 12,86 %, and 9,36 % respectively and also their antioxidant activity shown by values of IC50 of each: 43,36 ppm (1/IC50 = 0,023 ppm-1); 40,53 ppm (1/IC50 = 0,025 ppm-1); and 44,43 ppm (1/IC50 = 0,0225 ppm-1) respectively. These results indicated that Sentul fruit is very potential as an antioxidant.